1977
DOI: 10.1055/s-0028-1091566
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Cytomegalovirus Infection in Man

Abstract: SUMMARY In a prospective study of 148 children from urbanized southern Finland 3 were found to be congenitally and 48 perinatally infected with cytomegalovirus (CMV), while 6 developed 'late' infection during the first year of life. During pregnancy and the first year after delivery 23 of the mothers had no CMV antibodies; none of the children of these seronegative mothers developed any type of CMV infection. Fresh blood exchange transfusions did not increase the risk of CMV infection. The data support the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…Therefore, although CMI is not generally low in infants, the CMV-specific CMl diminishes for a long time during CMV infection. CMV infection in infants is usually acquired during the perinatal period [Ahlfors et al, 1978;Grangstrom et al, 1977;Leinikki et al, 1972;Levinsohn et al, 1969;Numazaki et al, 1970;Olson et al, 1970;Reynolds et al, 19731. Accordingly, CMI is generally weak or even absent at this age, and this is similar to the case of children with congenital infection [Gehrz et al, 1977;Okabe et al, 1983;Reynolds et al, 1979;Rola-Preszczynslu et al, 1977;Starr et al, 19791.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although CMI is not generally low in infants, the CMV-specific CMl diminishes for a long time during CMV infection. CMV infection in infants is usually acquired during the perinatal period [Ahlfors et al, 1978;Grangstrom et al, 1977;Leinikki et al, 1972;Levinsohn et al, 1969;Numazaki et al, 1970;Olson et al, 1970;Reynolds et al, 19731. Accordingly, CMI is generally weak or even absent at this age, and this is similar to the case of children with congenital infection [Gehrz et al, 1977;Okabe et al, 1983;Reynolds et al, 1979;Rola-Preszczynslu et al, 1977;Starr et al, 19791.…”
Section: Discussionmentioning
confidence: 99%
“…Active excretion of cytomegalovirus (CMV) is common among healthy infants who are perinatally infected with the virus [Ahlfors et al, 1978;Grangstrom et al, 1977;Leinikki et al, 1972;Levinsohn et al, 1969;Numazaki et al, 1970;Olson et al, 1970;Reynolds et al, 19731. It was found that among those infants shedding the virus antibodies increased after infection, but excretion of the virus did not cease for a long time after the appearance of antibodies [Ahlfors et al, 1978;Reynolds et al, 19731. This suggests that cessation of virus excretion in CMV infection among infants and children may not be a result of humoral immunity, but may result from another immune mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In populations of different ethnic and socioeconomic backgrounds, from 8-60% of infants are infected during the first six months of life [Whitley and Alford, 19791. Perinatal CMV infections were shown to be either asymptomatic or associated with respiratory syndromes, pneumonitis or hepatitis [Andersen et al, 1972;Stern, 1975;Granstrom et al, 1977;Ahlfors et al, 1978;Stagno et al, 1981;Panjvani and Hanshaw, 19811. CMV excreted in the endocervix, breast milk, and saliva were suggested to be the source of perinatal CMV infections and virus perpetuation [Hayes et al, 1972: Numazaki et al, 1970Reynolds et al, 1973: Granstriim et al, 1977Cabau et al, 1979;Stagno et al, 19811. Recently, in this laboratory, Pinku et al [1982] have demonstrated specific CMV-IgA antibodies in colostrum of 60% of CMV seropositive women by enzyme-linked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 99%
“…Midulla et al (1976) suggested that spasms are sometimes the result of an acquired, primary infection, but there is much evidence that acquired CMV infections generally cause no acute clinical symptoms and are without sequelae (Reynolds et aZ. 1973, Granstrom et al 1977.…”
Section: Discussionmentioning
confidence: 99%
“…Because CMV can be isolated from a high proportion of age-matched children in the normal population, it appears likely that CMV infection is only a parallel phenomenon to the infantile spasms and not a cau\al factor. For example, a recent study In Finland by Granstrom et al (1977) of SIX-to eight-month-old children found that 36 to 37 per cent were CMV excretors. In another study, Stern et al (1969) isolated CMV from the urine in six of 35 children with infantile spasms, but with such small numbers they could not establish a statistically significant difference from the ratio in age-matched controls.…”
Section: Introductionmentioning
confidence: 99%